Is good housekeeping the key to motor neuron survival? - Talbot, K; Davies, K (2008)
Spinal muscular atrophy (SMA) is caused by a drastic reduction in the ubiquitously expressed SMN protein, which is critical for the correct assembly of the snRNP complexes required for RNA splicing. However, it is unclear why loss of SMN and altered snRNP assembly only seem to affect motor neurons. Reporting in this issue, Zhang et al. (2008) challenge prior assumptions about the housekeeping function of SMN and demonstrate that loss of SMN leads to highly tissue-specific effects on splicing.